2020
DOI: 10.3390/diseases8020017
|View full text |Cite
|
Sign up to set email alerts
|

Association between Biofilm-Production and Antibiotic Resistance in Uropathogenic Escherichia coli (UPEC): An In Vitro Study

Abstract: Urinary tract infections (UTIs) are among the most common infections requiring medical attention worldwide. The production of biofilms is an important step in UTIs, not only from a mechanistic point of view, but this may also confer additional resistance, distinct from other aspects of multidrug resistance (MDR). A total of two hundred and fifty (n = 250) Escherichia coli isolates, originating from clean-catch urine samples, were included in this study. The isolates were classified into five groups: wild-type,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
50
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 67 publications
(62 citation statements)
references
References 62 publications
10
50
1
1
Order By: Relevance
“…The biofilm allows for the adherence of these pathogens on various surfaces, provides protection from harsh environmental conditions (e.g., sheer forces, drying), and from the immune system of the host (e.g., natural killer cells, phagocytes, complement, ROS-mediated damage) [75][76][77]. Biofilms have heterogenous compositions, consisting of aggregates of sessile bacterial communities (based on their composition, this may be monospecies or multispecies biofilm), exopolysaccharides (EPS; e.g., alginate, cellulose, dextran, rhamnolipids), environmental DNA (eDNA), carbohydrates, proteins, surfactants, lipids, various ions, and water [78,79]. The biofilm mode of growth was first described in the 1930s, while the true relevance of biofilm-embedded bacteria in infectious processes has been understood only in recent decades [80,81].…”
Section: Biofilm Formationmentioning
confidence: 99%
See 1 more Smart Citation
“…The biofilm allows for the adherence of these pathogens on various surfaces, provides protection from harsh environmental conditions (e.g., sheer forces, drying), and from the immune system of the host (e.g., natural killer cells, phagocytes, complement, ROS-mediated damage) [75][76][77]. Biofilms have heterogenous compositions, consisting of aggregates of sessile bacterial communities (based on their composition, this may be monospecies or multispecies biofilm), exopolysaccharides (EPS; e.g., alginate, cellulose, dextran, rhamnolipids), environmental DNA (eDNA), carbohydrates, proteins, surfactants, lipids, various ions, and water [78,79]. The biofilm mode of growth was first described in the 1930s, while the true relevance of biofilm-embedded bacteria in infectious processes has been understood only in recent decades [80,81].…”
Section: Biofilm Formationmentioning
confidence: 99%
“…Bacterial cells usually attach to hydrophobic and/or coarse surfaces with the aid of their cell-mediated virulence determinants (e.g., pili, fimbriae, surface antigens), which is followed by the production of the protective EPS and other components [82]. Biofilms allow P. aeruginosa to persist in the external environment (in water pipes and tanks, sinks, on hospital tiles, on medical equipment, such as mechanical ventilators and respiratory tubing, humidifiers, dialysis equipment and catheters, endoscopes and implanted medical devices, in medical preparations, such as irrigation solutions, dialysis fluid, contact lens fluid, antiseptic solution, cremes) and in vivo [75][76][77][78][79]83,84].…”
Section: Biofilm Formationmentioning
confidence: 99%
“…On the other hand, an adhesive molecule is a stand-alone surface protein, most commonly attached to the outer membrane or cell wall, the intrinsic structure of which facilitates the binding to a host receptor [ 28 ]. Adhesins are also involved in biofilm formation, antimicrobial resistance, and in the mechanism by which bacteria can be internalized within cells [ 25 , 26 , 27 , 29 ]. Hence, blocking the bacterial adhesins is the most preferred strategy for keeping the hosts safe from UTIs [ 30 ].…”
Section: The Importance Of Anti-adhesive Strategymentioning
confidence: 99%
“…In the present study, the incidence of biofilm formation in MDR ESBL-producing uropathogenic E. coli was 30% (n = 10). Published studies have reported a great variability in biofilm-production ability by urine-associated E. coli strains, ranging for 13 to 69% of total strains studied (n = 100-250) [33][34][35]. These variations can be explained by intrinsic differences among individual E. coli isolates as well as variations in the experimental conditions used to assess biofilm formation.…”
Section: Plos Onementioning
confidence: 99%